Mutations of Recombinant Aquaporin-4 Antibody in the Fc Domain Can Impair Complement-Dependent Cellular Cytotoxicity and Transplacental Transport - Mader, Simone; Brimberg, Lior; Soltys, John N.; Bennett, Jeffrey L.; Diamond, Betty (Frontiers in Immunology, 2018)
Maternal antibodies provide protection for the developing fetus. Transplacental transport of pathogenic autoantibodies might pose a risk for the developing fetus. The transport of antibodies across the placenta to the fetal circulation occurs through the neonatal Fc salvage receptor (FcRn). During gestation maternal autoantibodies are able to penetrate the embryonic brain before a functional intact blood brain barrier (BBB) is established. Brain-reactive antibodies to the water channel protein aquaporin-4 (AQP4) are a hallmark finding in neuromyelitis optica (NMO), a neurological disease that predominantly affects women, many of whom are of childbearing age. AQP4-IgG mediate astrocytic injury in a complement dependent fashion. Recent studies suggest these antibodies contribute to impaired pregnancy outcome. The aim of the study was to investigate the transplacental transport as well as FcRn binding of a monoclonal AQP4-IgG cloned from an NMO patient (wildtype antibody) compared to 5 different mutated Fc domain of this antibody containing single amino acid substitutions in the Fc region. All of the Fc mutated antibodies lack complement dependent cytotoxicity (CDC). Four of the five Fc mutated antibodies showed limited transplacental transport in vivo. Three mutated Fc with impaired transplacental transport showed persistent binding to rodent FcRn at pH 6 but also at pH 7.2, suggesting that limited transplacental transport could be due to diminished release from FcRn. One mutated Fc with modestly limited transplacental transport showed diminished binding to FcRn at pH 6. This study suggests that mutated Fc with intact transplacental transport may be used to study antibody effector functions and Fc with limited transport may be used as a carrier to deliver therapies to pregnant woman, while sparing the developing fetus.